Isolasi Lignin dari Serbuk Grajen Kayu Jati (Tectona Grandis) dengan Metode Klasson - Priyono Kusumo; S Biyono; Tegar S (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2020)
Isolation of lignin from Jepara teak furniture waste is an effort to utilize this waste and to overcome environmental pollution. Lignin was isolated by extraction from the sawdust of furniture waste, hydrolyzed and identified by Fourier Transport Infra-Red (FTIR). Isolation was carried out with a sample weight of 10 grams, a time of 2 hours and a temperature of 110oC and variations in the concentration of NaOH. The lignin yield of 0,106% (1,06 g) was obtained at a concentration of 12%-w NaOH, time of 2 hours and a temperature of 110oC. The guacil functional group as the dominated element of the lignin compounds was identified by FTIR spectra results at the absorption wavelength of 1269,6 cm-1.